Dynamic Manning's roughness coefficients for hydrological modelling in basins - Ye, Aizhong; Zhou, Zheng; You, Jinjun; Ma, Feng; Duan, Qingyun (Hydrology Research, 2018)
Manning's roughness coefficient (n) has a significant impact on routing in hydrological models. However, computational methods for dynamic roughness coefficients are of little concern in current research. Few studies have produced spatial-temporal distributions of the roughness coefficients in basins. In this study, a formula to calculate the n value was established based on a statistical analysis of estimated n values by Manning's formula. The routing model of a distributed hydrological model was then improved using the new formula to calculate n. The roughness coefficient is not a constant; instead, it changes dynamically with changes in water depth and vegetation in the improved hydrological model. The improved model was applied to the Yellow River basin. The results show that using dynamic n can improve the streamflow simulation of hydrological models, especially on slopes. The dynamic spatial-temporal distribution of n can now be used in other models.